Aspects of conflicts within the organization - Georgieva, Ivona; Georgieva, Slavka (Vilnius University Open Series, 2019)
The article focuses on some of the aspects of conflicts within the organization. Issues leading to conflicts are discussed as an integral part of organizational life. The main types of conflicts are characterized. It is emphasized that regardless of the outcome of the conflict, its consequences have a certain impact and that each organization could benefit even from the conflict. There is no universal way of correct resolution, it depends on the conflict itself, the individual characteristics of each of the team members and, above all, the correct approach of the leaders. Failure to listen and downplaying the other side does not solve the problem. The best way out of conflict is solving the problem that caused the conflict.
Keywords: organization; conflict resolution strategies